2016
DOI: 10.1186/s13019-016-0472-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic monitoring of platelet activation and its role in post-dissection inflammation in a canine model of acute type A aortic dissection

Abstract: BackgroundTo confirm the activation of platelets (PLT) and explore the role of activated PLT in post-dissection inflammation.MethodAn acute type A aortic dissection (AAD) canine model was established. Mean platelet volume/platelet count (MPV/PTC), platelet size distribution width (PDW), and inflammatory cytokines (tumor necrosis factor-α [TNF-α] and interleukin-6 [IL-6]) were measured between anesthetization and thoracotomy (T1), at the end of the operation (T2), and at 2 h (T3), 4 h (T4), and 6 h (T5) after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
2
8
0
1
Order By: Relevance
“…It has also been demonstrated that an inflammatory reaction can destroy the medial layer of the aorta and eventually lead to dilation, dissection and rupture of aortic wall [ 23 , 24 ]. Moreover, local inflammation in aortic wall and systemic inflammatory responses were observed during the whole course of AAD [ 9 , 10 , 25 ]. TLR4 is a useful marker for evaluating inflammatory response and vascular injury, and its activation plays a critical role in vascular remodeling [ 12 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that an inflammatory reaction can destroy the medial layer of the aorta and eventually lead to dilation, dissection and rupture of aortic wall [ 23 , 24 ]. Moreover, local inflammation in aortic wall and systemic inflammatory responses were observed during the whole course of AAD [ 9 , 10 , 25 ]. TLR4 is a useful marker for evaluating inflammatory response and vascular injury, and its activation plays a critical role in vascular remodeling [ 12 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…[2627] Qin et al . [28] have recently dynamically monitored the systemic inflammatory level and platelet activation with a new acute TAAD canine model. Their study found that both tumor necrosis factor-α and IL-6 were significantly climbed and reached highest levels at 6 h after the AD model was established.…”
Section: Discussionmentioning
confidence: 99%
“…The activated PLT in the false lumens form a thrombus, resulting in a drop in the PLT count in the body. Chaoyi Qin et al [13] proved that the PLT count (K/ul) in aortic dissection is lower than chronic aortic aneurysm and healthy people. This change of PLT count may be related to extent of dissection, and is consistent with the findings of earlier study by Tanaka et al [14].…”
Section: Discussionmentioning
confidence: 99%